Consensus recommendations on the use of daylight photodynamic therapy with methyl aminolevulinate cream for actinic keratoses in Australia. (31st May 2015) - See, Jo‐Ann; Shumack, Stephen; Murrell, Dedee F; Rubel, Diana M; Fernández‐Peñas, Pablo; Salmon, Robert; Hewitt, Daniel; Foley, Peter; Spelman, Lynda
Abstract: Australia has the highest prevalence of actinic keratoses (AK) worldwide. Because of the risk of transformation of AK to invasive squamous cell carcinomas, consensus guidelines recommend that AK are removed using appropriate therapies to prevent progression to invasive disease. Daylight photodynamic therapy (PDT) is emerging as an efficacious treatment for AK, particularly for patients who require treatment of large areas of chronic actinic damage that can be exposed easily to daylight. Daylight PDT with methyl aminolevulinate (MAL) cream is a simple treatment for AK, almost painless, well tolerated and convenient, requiring minimal time in the clinic. Randomised controlled studies from northern Europe and Australia support the use of daylight PDT as an effective therapy for grade I and II AK on the face and scalp. There is sufficient daylight to conduct daylight PDT in Australia at any time of the year and during most weather conditions. Hence, daylight PDT with MAL can be included as an effective and well‐tolerated new treatment option for the treatment of AK in Australia. These consensus recommendations provide guidelines for Australian clinicians on the use of daylight PDT in the treatment of diagnosed AK.